2021
DOI: 10.1159/000515086
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Transglutaminase Impairs HTR-8/SVneo Trophoblast Cell Invasion via the PI3K/AKT Signaling Pathway

Abstract: <b><i>Objectives:</i></b> The pathogenesis of preeclampsia (PE) is associated with impaired trophoblast invasion, which results in placental insufficiency. Our earlier studies demonstrated that tissue transglutaminase (tTG) is highly expressed in human PE serum. However, whether tTG participates in trophoblast invasion remains unclear. The aim of the present study was to determine the role and mechanism of tTG in regulating matrix metalloproteinase (MMP)-2/MMP-9 expression to reduce tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…These investigations have explored factors including inflammatory immune hyperactivation, lipid metabolism abnormalities, and inadequacies in uterine spiral artery remodeling. The diagnostic markers include the PI3K/AKT signaling pathway, [ 11 ] IL-15, [ 12 ] HMGB1-TLR4, [ 13 ] adiponectin, [ 14 ] uric acid, [ 15 ] and uterine artery flow doppler indices. [ 16 ] Both PE and FGR originate from placental factors, manifesting months before clinical diagnosis occurs.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations have explored factors including inflammatory immune hyperactivation, lipid metabolism abnormalities, and inadequacies in uterine spiral artery remodeling. The diagnostic markers include the PI3K/AKT signaling pathway, [ 11 ] IL-15, [ 12 ] HMGB1-TLR4, [ 13 ] adiponectin, [ 14 ] uric acid, [ 15 ] and uterine artery flow doppler indices. [ 16 ] Both PE and FGR originate from placental factors, manifesting months before clinical diagnosis occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the activated PI3K/AKT pathway in PE placentas is involved in trophoblast cell proliferation 21,22 . Besides, PI3K/AKT signaling is also involved in the regulatiion of trophoblast migration and invasion 23,24 . DR3 has been reported to be the upstream of PI3K 17 .…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Besides, PI3K/AKT signaling is also involved in the regulatiion of trophoblast migration and invasion. 23 , 24 DR3 has been reported to be the upstream of PI3K. 17 Therefore, we hypothesized that DR3 may affect the physiology of placental trophoblasts by regulating the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%